2022
DOI: 10.3847/2041-8213/ac8880
|View full text |Cite
|
Sign up to set email alerts
|

Misaligned Circumbinary Disks as Efficient Progenitors of Interstellar Asteroids

Abstract: Gaseous circumbinary disks (CBDs) that are highly inclined to the binary orbit are commonly observed in nature. These disks harbor particles that can reach large mutual inclinations as a result of nodal precession once the gas disk has dissipated. With n-body simulations that include fragmentation we demonstrate that misaligned disks of particles can be efficient progenitors of interstellar asteroids (ISAs). Collisions that take place between particles with large mutual inclinations have large impact velocitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Formation of terrestrial planets from a misaligned disc of planetestimals after the gas disc has dissipated may also be difficult, unless the disc is close to coplanar or polar alignment (Childs & Martin 2021a,b, 2022a. A highly misaligned disc of planetesimals around a binary may be largely ejected (Childs & Martin 2022b). Therefore, multiple low mass CBP systems may be not applicable for our study.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of terrestrial planets from a misaligned disc of planetestimals after the gas disc has dissipated may also be difficult, unless the disc is close to coplanar or polar alignment (Childs & Martin 2021a,b, 2022a. A highly misaligned disc of planetesimals around a binary may be largely ejected (Childs & Martin 2022b). Therefore, multiple low mass CBP systems may be not applicable for our study.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed studies by Veras & Tout (2012) and Veras et al (2014) found that exocomets are more likely to escape from post-main-sequence binaries than from single stars, especially for wide-separation and eccentric stellar companions. Notably, binary stars have been proposed as prolific producers of interstellar small bodies (Ćuk 2018;Jackson et al 2018;Childs & Martin 2022) during the (pre-)main-sequence. Planetary perturbers could similarly affect ejection fractions, and indeed a population of giant planets is required to generate the initial exo-Oort Clouds (Dones et al 2004).…”
Section: Other Dynamical Considerationsmentioning
confidence: 99%
“…Even widely spaced planetary systems can be unstable around a tilted binary (see Section 2.2). Thus the ejection of planets from a misaligned binary system can be far more efficient compared to a single star or coplanar binary system (see also Childs & Martin 2022).…”
Section: Introductionmentioning
confidence: 99%